2008
DOI: 10.1111/j.1442-2042.2008.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inguinal hernia after prostate surgery: Open radical retropubic prostatectomy versus open simple prostatectomy versus transurethral resection of the prostate

Abstract: Abstract:Our objective was to determine the incidence of inguinal hernia (IH) after surgery for prostatic diseases. Medical records of 395 patients who underwent radical retropubic prostatectomy (RRP; n = 155), open simple prostatectomy (OP; n = 35), or transurethral resection of the prostate (TURP; n = 205) at the Chibaken Saiseikai Narashino Hospital from April 2000 to March 2007 were retrospectively evaluated. The incidence of IH was 23.9% in the RRP group, 18.9% in the OP group, and 2% in the TURP group. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 12 publications
0
44
0
2
Order By: Relevance
“…One study reported a significant relationship between postoperative wound-related problems and the development of IH after RRP [16]. No study has ever shown evidence linking prostate volume [3,4,16], duration of surgery [17] or smoking history [16] to the development of IH after RP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a significant relationship between postoperative wound-related problems and the development of IH after RRP [16]. No study has ever shown evidence linking prostate volume [3,4,16], duration of surgery [17] or smoking history [16] to the development of IH after RP.…”
Section: Discussionmentioning
confidence: 99%
“…Inguinal hernias (IHs) develop in 8.6-23.9% of men undergoing open radical retropubic prostatectomy (ORRP) [1][2][3][4][5]. This high rate of IHs after ORRP led to the conclusion that the surgical procedure was the direct cause of these IHs.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of inguinal hernia is as high as after simple open prostatectomy for BPH that is not accompanied by resection of endopelvic fascia. 7 The incidence was not significantly reduced by the modified RRP, in which both vasa deferentia and surrounding tissues were dissected before placing the retractor so as not to retract them and injure the myopectineal orifice. 8 Most ideas about the altered anatomical structure of fascia or muscle have been controversial to date, and it seems to be difficult to attribute a single cause to inguinal hernia.…”
Section: -15mentioning
confidence: 99%
“…Age 5,6,9,[15][16][17][18]20 and anastomic stricture 9,14,17,18,20,21 have been suggested as risk factors in some studies, but not in others. Resection of endopelvic fascia 7 and retraction of the vasa deferentia by a retractor 8 are probably not the causative factors. The incidence of inguinal hernia is as high as after simple open prostatectomy for BPH that is not accompanied by resection of endopelvic fascia.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation